Arthritic Japan : - Lincoln, Edward J. (Brookings Institution Press, 2001)
This is a timely book on the prospects for meaningful structural reform in the world's second largest economy, written by a long-time observer of Japan who served as a special advisor to Ambassador Walter Mondale in the Tokyo emabssy in the mid-1990s